2012
DOI: 10.1007/s13592-012-0154-9
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of bee bread made by Africanized and European honey bees (Apis mellifera) and its effects on hemolymph protein titers

Abstract: -The influence of genotype on the conversion of pollen to bee bread and on the protein titers of bees feeding on it was examined using European and Africanized honey bees (EHB and AHB). Bee bread was more acidic than the pollen, and that made by EHB was slightly more acidic than AHB. Protein concentration in bee bread was similar for both subspecies and lower than in the pollen. In general, amino acid concentrations were higher in bee bread compared with pollen. The only exception was tryptophan. Concentration… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
54
1
3

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 64 publications
(62 citation statements)
references
References 57 publications
4
54
1
3
Order By: Relevance
“…The beebread might have had pollen from sources other than rapini and caused the differences. However, similar results from controlled feeding studies have been reported (Human and Nicolson 2006;DeGrandi-Hoffman et al 2013). Possible reasons include the activity of proteolytic enzymes added to pollen during storage and metabolism by microbes in stored pollen (Gilliam et al 1989;Metges 2000).…”
Section: Discussionsupporting
confidence: 69%
“…The beebread might have had pollen from sources other than rapini and caused the differences. However, similar results from controlled feeding studies have been reported (Human and Nicolson 2006;DeGrandi-Hoffman et al 2013). Possible reasons include the activity of proteolytic enzymes added to pollen during storage and metabolism by microbes in stored pollen (Gilliam et al 1989;Metges 2000).…”
Section: Discussionsupporting
confidence: 69%
“…L. kunkeei bacteria also play a key role in the lactic acid fermentation of pollen to bee bread due to their acid-, oxygen-, and osmo-tolerant features and are among the small subset of bacteria isolated from pure honey (25,40). Although the mechanisms underlying the bee bread production are not completely elucidated, LAB have been supposed to affect the pollen maturation process lowering the pH and modifying the sugar and amino acid profiles (25,41). This study aimed at investigating the metabolism of phenolic acids by FLAB as a potential alternative energy route using a high-throughput phenotypic microarray targeting 190 carbon sources.…”
mentioning
confidence: 99%
“…Hemolymph collection and total soluble protein analysis We compared hemolymph protein concentrations between treatments as a measure of protein uptake in a manner similar to other studies (e.g., Bitondi and Simoes 1996;Cremonez et al 1998;Cappelari et al 2009;DeGrandi-Hoffman et al 2013). Hemolymph was extracted from ice-anesthetized workers (newly emerged bees, 7-day-old caged bees, nurse bees, and pollen foragers) using 100-μL microcapillary pipettes (Kimble Glass, Inc.) which had previously been held over a Bunsen burner flame and then pulled apart to form a sharp tip.…”
Section: Methodsmentioning
confidence: 99%